2016
DOI: 10.1007/s11557-016-1257-x
|View full text |Cite
|
Sign up to set email alerts
|

The plasticity of fungal interactions

Abstract: Their hyphal structure, the common events of hybridization and horizontal gene transfer, as well as intimate associations with prokaryotes (including endobiotic bacteria) and cooperation with eukaryotes have made fungi very flexible at the genetic, physiological, and ecological levels. It is manifested with the fungal ability to perfectly exploit existing nutrient sources and plastically fit into a changing environment. Although the links between fungi and other ecosystem components are rarely clearly visible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 80 publications
(86 reference statements)
3
10
0
1
Order By: Relevance
“…This confirms the thesis that without computed tomographic assessment of the interior of the wood, trees infected with the pathogen can grow unproductively for decades as commodities in managed spruce stands [19,37,104,105]. Another question is their ecological role in the ecosystem, where the pathogen and the resulting decomposition of wood during forest succession can provide suitable opportunities for the development of other organisms such as other fungi, birds, bats, insects, and squirrels [106][107][108][109][110].…”
Section: Discussionsupporting
confidence: 65%
“…This confirms the thesis that without computed tomographic assessment of the interior of the wood, trees infected with the pathogen can grow unproductively for decades as commodities in managed spruce stands [19,37,104,105]. Another question is their ecological role in the ecosystem, where the pathogen and the resulting decomposition of wood during forest succession can provide suitable opportunities for the development of other organisms such as other fungi, birds, bats, insects, and squirrels [106][107][108][109][110].…”
Section: Discussionsupporting
confidence: 65%
“…Genera of the Hypocreaceae have morphological features that differentiate them from one another (Jaklitsch et al 2008 ; Jaklitsch 2009 ; Põldmaa 2011 ). Due to the morphological plasticity of fungi (Slepecky and Starmer 2009 ; Wrzosek et al 2017 ), variations in the shades of colours expressed by these organisms are highly expected. Nonetheless, the prevalent brown colour of Escovopsis colonies is a unique feature of this genus within the family.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this fact made it difficult to describe new species of the parasite. Studies showed that the expressed phenotypic characters (phenotypic plasticity) of fungi are directly influenced by growth conditions (Slepecky and Starmer 2009, Sharma and Pandey 2010, Wrzosek et al 2017, Kim et al 2017). As the morphological plasticity of Escovopsis species is still poorly understood, the standardisation of cultivation conditions is imperative.…”
Section: Discussionmentioning
confidence: 99%